Computerized content analysis to approach the concept of objectivity maintained by professional journalists in Spain - Barredo Ibáñez, Daniel (2015)
The idea of objectivity that Spanish journalists have (i.e. women and men who work as journalists) is analyzed in this paper since this is one of the main concepts that shape the values and ideas of the journalism culture in a country. First, a qualitative study was conducted with a representative sample of 19 journalists of Spanish origin from different organizations or media (press, radio, television and digital media). The methodology used, the in depth interview, offered the possibility to gather information on specific issues, particularly the individual perception of objectivity. Second, responses were studied using a computerized content analysis of lexical associations between the most frequent terms. Through the triangulation of both methods (qualitative and quantitative) the authors showed, as results, the elements that form the backbone of the concept of objectivity for the interviewed Spanish journalistic community. In addition, another major finding resulting from this research was the instrumental description, which included a combination of very novel techniques.